Relied upon for the heavy lifting: can employment protection legislation reforms lead the EU out of the jobs crisis?. Issue 2 (16th February 2015) - Heyes, Jason; Lewis, Paul
Abstract: This article examines the current drive within the European Union to weaken employment protection legislation. It subjects the case for reform to critical scrutiny and argues that labour market deregulation and the erosion of employment and social protections are reducing workers' security while failing to stimulate economic recovery.